Pendidikan Kewirausahaan Berbasis Gender Dalam Perspektif Al-Qur’an - Ruslan, Muhammad (Alif Lam : Journal of Islamic Studies and Humanities, 2023)
To become an entrepreneur, the first thing to prepare is to master the knowledge of entrepreneurship, know the basic concepts of entrepreneurship and the ins and outs of it. An entrepreneur requires a strong mentality and a creative, innovative and courageous spirit to face challenges in the future. To become an entrepreneur is not bound by a certain gender, anyone has the right to become an entrepreneur without any differences in ethnicity, race and gender. Men and women are created in pairs and both are partners who complement each other. It should be noted that, long before there were balance theories about men and women in entrepreneurship, the Qur'an had previously reported on this theory, this is mentioned in the Qur'an in surah An-Nisa/4: 32 and surah an-nahl/16: 97, explicitly states that: men and women have equal access and opportunities to become entrepreneurs. The balance of roles between men and women in entrepreneurship is a necessity, because both are creatures that were created to complement each other, have the same potential and both come from the same creation and origin, and both have the same abilities. in doing whatever they want